Pernikahan Dibawah Tangan Dalam Tinjauan Maqasid al-Syariah dan Utilitarianisme - Erni Juniyati; Miftakur Rohman (MASADIR: Jurnal Hukum Islam, 2023)
Private marriages are marriages carried out by Muslims who fulfill the pillars and requirements of marriage, but are not registered with the Marriage Registrar as regulated in Law no. 1 of 1974 concerning Marriage. This marriage is actually valid if it meets the marriage requirements according to Islamic law. It's just that formally, juridically, it doesn't meet the requirements of the provisions regulated in Law no. 1 of 1974 and its implementing regulations, namely that it is not registered with the Marriage Registrar's Office. So the impact that arises from this underhanded marriage is that the wife is not entitled to alimony, inheritance, shared assets. Apart from that, the status of the child born is considered an illegitimate child. As a consequence, the child only has a civil relationship with the mother and the mother's family. This research is a type of normative research. The nature of the research is descriptive qualitative, namely describing underhanded marriages based on Maq??id Al-Shar?'ah and Utilitarianism. The research results show that marriage under the hand is not in accordance with Maq??id Al-Shar?'ah because it is contrary to the benefit of human al-?ar?r?yah, namely religion, soul, reason, lineage and property. This marriage is also incompatible with Utilitarianism because it is not in accordance with the principle of happiness.